2022
DOI: 10.3390/ijms23084352
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Dendritic Cells and Sirtuins in Multiple Sclerosis

Abstract: Myeloid cells, including parenchymal microglia, perivascular and meningeal macrophages, and dendritic cells (DCs), are present in the central nervous system (CNS) and establish an intricate relationship with other cells, playing a crucial role both in health and in neurological diseases. In this context, DCs are critical to orchestrating the immune response linking the innate and adaptive immune systems. Under steady-state conditions, DCs patrol the CNS, sampling their local environment and acting as sentinels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 223 publications
0
14
0
Order By: Relevance
“…B cell depletion may reduce the proinflammatory cytokines produced by B cells, CD4+ and CD8 + T cells which can effectively reduce MS relapses 86,87 . NK and DC cells control T cell activation in CNS autoimmunity, and reduced the risk of MS 88,89 . Mast cells participate in the pathogenesis of MS by promoting angiogenesis 90 .…”
Section: Discussionmentioning
confidence: 99%
“…B cell depletion may reduce the proinflammatory cytokines produced by B cells, CD4+ and CD8 + T cells which can effectively reduce MS relapses 86,87 . NK and DC cells control T cell activation in CNS autoimmunity, and reduced the risk of MS 88,89 . Mast cells participate in the pathogenesis of MS by promoting angiogenesis 90 .…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed by Piacente et al, sirtuin 1 (SIRT1) and sirtuin 2 (SIRT2), which are NAD + -dependent deacetylases, possibly play a role in regulating neuroinflammation and microglial activation in MS [ 153 ]. Studies of SIRT2 using LPS-induced neuroinflammation have yielded conflicting results, with one group demonstrating SIRT2 −/− mice experiencing an increase in pro-inflammatory cytokines and morphological changes in microglia, while another group found that administration of an SIRT2 inhibitor significantly reduced microglial activation, as well as TNF-α and IL-6 expression [ 153 , 154 , 155 ]. Current research on SIRT1 is more cohesive, however, with several groups reporting that SIRT1 may promote the transformation of activated microglia from a pro-inflammatory M1-like phenotype to a neuroprotective M2-like phenotype in EAE mice [ 153 , 156 , 157 ].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Studies of SIRT2 using LPS-induced neuroinflammation have yielded conflicting results, with one group demonstrating SIRT2 −/− mice experiencing an increase in pro-inflammatory cytokines and morphological changes in microglia, while another group found that administration of an SIRT2 inhibitor significantly reduced microglial activation, as well as TNF-α and IL-6 expression [ 153 , 154 , 155 ]. Current research on SIRT1 is more cohesive, however, with several groups reporting that SIRT1 may promote the transformation of activated microglia from a pro-inflammatory M1-like phenotype to a neuroprotective M2-like phenotype in EAE mice [ 153 , 156 , 157 ]. Additionally, SIRT1 may play a role in regulating inflammation, as upregulation of SIRT1 in LPS-treated microglial cell line has been shown to attenuate the expression of IL-1β and IL-6 [ 153 , 158 ].…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…SIRTs deserve attention regarding MS pathology as relevant regulators of the main processes involved in the background of the disease: (auto)immune response, neurodegeneration, and metabolic pathway [ 126 ]. The activity of SIRTs was extensively investigated in experimental autoimmune encephalomyelitis (EAE), which is a widely used animal model of MS, and more recently also in clinical studies involving MS subjects.…”
Section: Sirts In Cns Diseasesmentioning
confidence: 99%
“…Inhibition of SIRT6 delayed EAE onset by early downregulation of CD40 expression on DCs and T cells infiltration in the CNS. In studies on MS subjects in the earliest phase of disease, presenting with high levels of DCs in peripheral blood, SIRT6 inhibition was demonstrated to interfere with DCs migration and delay conversion from clinically isolated syndrome (first clinical manifestation) to the relapsing-remitting stage of disease [ 126 ]. The role of SIRT7 in MS has been less recognized.…”
Section: Sirts In Cns Diseasesmentioning
confidence: 99%